Module 2: Islamic Psychology of Education - Wan Yusoff, Wan Mazwati; Mansor, Norwati (2021)
This module is developed based on reviews of the literature on Islamic psychology of education by prominent scholars such as Imam al-Ghazali, al-Balkhi, al-Attas, and Malik Badri. Western perspectives on psychology were also reviewed comparatively from the Islamic viewpoint. From experience and observation, educational psychology that is being taught to trainee teachers in higher education institutions is largely from a western perspective. This is very unfortunate since what drives Muslims to behave the way they do are different from non-Muslims. Muslims view life as a unified whole—not compartmentalised into distinct areas—with the main purpose of gaining Allah’s pleasure. Furthermore, Islam defines key concepts in psychology differently from Westerners since the main sources of knowledge in Islam is Quran and Sunnah. This is so because Muslims believe that Allah is the creator of humans, therefore it is logically followed that knowledge about humans should come from the Creator especially knowledge on the spiritual dimension of humans. The module provides explanations on learners and how they learn from the Islamic perspective. Understanding the nature of learners from an Islamic perspective is important to guide teachers in the implementation of holistic education.